2018
DOI: 10.1007/s00436-018-5919-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of parasitic protozoa and Ehrlichia canis in wildlife in Madrid (central Spain)

Abstract: Wildlife species are involved in the transmission of diverse pathogens. This study aimed to monitor raccoons (Procyon lotor), American minks (Neovison vison), and red foxes (Vulpes vulpes) as potential reservoirs in central Spain. Specifically, 200 spleen and fecal samples (from 194 raccoons, 3 minks, and 3 foxes) were analyzed molecularly by PCR/qPCR and sequencing for the presence of piroplasmids, Hepatozoon spp., Toxoplasma gondii, and Ehrlichia canis infections in the Community of Madrid (Spain). Biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Among wild felids, E. canis rrs has been detected in ocelots ( Leopardus pardalis ) (13.3–17.2%), jaguarondis ( Herpailurus yagouaroundi ) (10.5–16.6%), little spotted cats ( Leopardus tigrinus ) (8.0–14.3%), pumas ( Puma concolor ) (1.1–25%), jaguars ( Panthera onca ) (22.2%), lion ( Panthera leo ) (16.6%) maintained in captivity in zoos in Brazil ( 75 , 9 ), free-ranging Iriomote cats (12%) ( Prionailurus iriomotensis ) and Tsushima leopard cats ( Prionailurus bengalensis euptilura ) (8%) in Japan ( 47 ), and lions (1%) maintained in captivity in Zimbabwe ( 42 ) (Table 2 ). Among procyonids and mustelids, E. canis rrs has been detected in raccoons ( Procyon lotor ) (1.7%) from the USA ( 78 ) and Spain (2.6%) ( 36 ), coatis (3.2%) from Brazil ( 12 ), and Eurasian otters (50%) from Italy ( 73 ) (Table 2 ). Although E. canis rrs has been detected in several wild captive felid species in Brazil ( 75 ), phylogenetic analysis based on omp-1 gene positioned Ehrlichia sp.…”
Section: Molecular Prevalence and Diversity Of Tick-borne Anaplasmatamentioning
confidence: 99%
See 2 more Smart Citations
“…Among wild felids, E. canis rrs has been detected in ocelots ( Leopardus pardalis ) (13.3–17.2%), jaguarondis ( Herpailurus yagouaroundi ) (10.5–16.6%), little spotted cats ( Leopardus tigrinus ) (8.0–14.3%), pumas ( Puma concolor ) (1.1–25%), jaguars ( Panthera onca ) (22.2%), lion ( Panthera leo ) (16.6%) maintained in captivity in zoos in Brazil ( 75 , 9 ), free-ranging Iriomote cats (12%) ( Prionailurus iriomotensis ) and Tsushima leopard cats ( Prionailurus bengalensis euptilura ) (8%) in Japan ( 47 ), and lions (1%) maintained in captivity in Zimbabwe ( 42 ) (Table 2 ). Among procyonids and mustelids, E. canis rrs has been detected in raccoons ( Procyon lotor ) (1.7%) from the USA ( 78 ) and Spain (2.6%) ( 36 ), coatis (3.2%) from Brazil ( 12 ), and Eurasian otters (50%) from Italy ( 73 ) (Table 2 ). Although E. canis rrs has been detected in several wild captive felid species in Brazil ( 75 ), phylogenetic analysis based on omp-1 gene positioned Ehrlichia sp.…”
Section: Molecular Prevalence and Diversity Of Tick-borne Anaplasmatamentioning
confidence: 99%
“…Although E. canis has been molecularly detected in free-ranging raccoons from the USA (1.7%) ( 78 ) and Spain (2.6%) ( 36 ), Yabsley et al ( 52 ) showed that Procyon lotor was not susceptible to experimental infection with E. canis . In the USA, although D. variabilis , a recognized vector for E. canis ( 64 ), has been found parasitizing dogs and medium-sized wild mammals, such as raccoons ( 52 , 61 , 78 ), allowing for E. canis inter-species transmission in suburban areas, raccoons seem to play a limited role as a vertebrate reservoir for this agent in the USA ( 78 ).…”
Section: Molecular Prevalence and Diversity Of Tick-borne Anaplasmatamentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, studies on Echinococcus multilocularis (14 studies, three species), Toxoplasma gondii (nine studies, six species), and Baylisascaris procyonis (nine studies, one species) were particularly abundant among the study species (Appendix S5). Prevalence rates presented a high geographical and taxonomical variability: the prevalence of E. multilocularis ranged between 0% (in the raccoon and the raccoon dog in various countries; Kornyushin et al 2011, Wahlström et al 2012, EFSA 2015, Oksanen et al 2016, Duscher et al 2017) and 28% (in the racoon dog in Slovakia; Oksanen et al 2016); for T. gondii, it ranged from 0% (in mink in Spain and the raccoon in the Czech Republic; Criado-Fornelio et al 2018, Kornacka et al 2018) to 78.8% (in mink in Spain; Ribas et al 2018); lastly, the prevalence of B. procyonis in raccoons ranged from 1.9% in Poland (Karamon et al 2014) to 80% in Germany (Hohmann et al 2002). Moreover, there are recent reports from Denmark and the Netherlands regarding SARS-CoV-2 infection in minks (Oreshkova et al 2020).…”
Section: Environmental and Socio-economic Impacts In Europementioning
confidence: 99%
“…CC-BY 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted April 22, 2021. ; https://doi.org/10.1101/2021.04.21.440832 doi: bioRxiv preprint 13 countries; Kornyushin et al 2011, Wahlström et al 2012, EFSA 2015, Oksanen et al 2016, Duscher et al 2017) and 28% (in the racoon dog in Slovakia; Oksanen et al 2016); for T. gondii, it ranged from 0% (in mink in Spain and the raccoon in the Czech Republic; Criado-Fornelio et al 2018, Kornacka et al 2018) to 78.8% (in mink in Spain; Ribas et al 2018); lastly, the prevalence of B. procyonis in raccoons ranged from 1.9% in Poland (Karamon et al 2014) to 80% in Germany (Hohmann et al 2002). Moreover, there are recent reports from Denmark and the Netherlands regarding SARS-CoV-2 infection in minks (Oreshkova et al 2020).…”
Section: Environmental and Socio-economic Impacts In Europementioning
confidence: 99%